Impact of the Advanced Awareness Program on Insight Level Regarding Occupational Hazards Prevention between Industrial Employees from Selected Private Ahmednagar Industry - Rajesh Salvi, Jayashree (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study to assess the impact of advanced awareness program on insight level regarding occupational hazards prevention between industrial employees. Materials and Methods: The design adopted for the study is pre-experimental design with one group pre-tests and post-test design with the quantitative research approach was used to judge the impact of the advanced awareness program on insight level regarding occupational hazards prevention between industrial employees from selected private Ahmednagar industry. The sample size comprised of 300 rural health care workers fulfilling the inclusion and exclusion criteria. The non-probability convenient sampling technique was used for selection of samples. Insight level regarding occupational hazards prevention was assessed using the knowledge questioners, open-ended questions. Data were analyzed using the descriptive and inferential statistics. Results: There is a statistically significant mean difference between pre- and post-insight level scores as the calculated t-value is 85.84 (P = 0.0026) which is more than the t-value of 1.08 at a level of significance of 0.05 with a degree of freedom being 281. The knowledge among the health workers has been increased after providing the awareness program on the level of insight regarding occupational hazard prevention between industrial employees. Conclusion: The study concludes that the knowledge and the insight level among the health workers have been increased after providing the awareness program regarding occupational hazard prevention between industrial employees.